Caracterização funcional de HTRA1 em linhagens celulares HPV positiva e HPV negativa - Stuqui, Bruna [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The Human Papillomavirus (HPV) is one of the most prevalent virus among sexually transmitted infections and it is associated with some malignancies. High risk HPVs contain proteins, E6 and E7, characterized by oncoproteins due to their roles in cellular transformation and suppressor tumor inactivation. One of the mechanisms used in cell transformation by E6 protein from high-risk HPVs is the interaction of its carboxy-terminal domain, known as PDZ, with PDZs domains present in some cellular proteins, triggering them to degradation. A protein that is associated with various pathological conditions and has PDZ domain is the protease HtrA1. This protein is poorly expressed in some cancers, suggesting its tumor suppressor role. The aim of this study was to evaluate the effect of the HtrA1 overexpression in HPV 16 positive (HF698) and HPV negative (C33) cell lines. The cell lines were transfected with vector containing the HTRA1 ORF or empty vector. The mRNA and protein overexpression were confirmed by qPCR and immunohistochemical, respectively. The cell lines transfected were subjected to cell proliferation, viability, apoptosis and cell cycle assays. C33 cells expressing HtrA1 presented significantly fewer colonies and showed reduced viability than cells without HtrA1 expression. On the other hand, in HPV-positive cell line there was an increase in the number of colonies in cells expressing HtrA1 and there was no difference in the cell viability assay. These results suggest that the different patterns observed between the two cell lines studied may be due to the HPV presence in HF698 and its absence in C33 cells. To confirm if the increase in the number of colonies in HPV positive cells (HF698) overexpressing HtrA1 arises from the interaction of this protein with E6, stable lines of C33 containing gene E6 were produced and subsequently performed cell proliferation assay. C33 cells overexpressing E6 and HTRA1 showed an increased number of ...

O Papilomavirus humano (HPV) é um dos vírus mais prevalentes entre as infecções sexualmente transmissíveis e está associado com doenças malignas. Os HPVs de alto risco possuem proteínas, denominadas de E6 e E7, caracterizadas como oncoproteínas devido aos seus papéis na transformação celular e na inativação de supressores de tumor. Um dos mecanismos usados na transformação celular pela proteína E6 do HPV de alto risco é a interação do seu domínio carboxi-terminal, PDZ, com domínios PDZs presentes em algumas proteínas celulares, destinando-as à degradação. Uma proteína que está associada com várias condições patológicas e tem domínio PDZ é a protease HtrA1. Esta proteína é pouco expressa em alguns cânceres, sugerindo um papel supressor de tumor. O objetivo deste estudo foi avaliar o efeito da superexpressão de HTRA1 em linhagem celular HPV16 positiva (HF698) e HPV negativa (C33). As linhagens celulares foram transfectadas com vetor contendo a ORF de HTRA1 ou vetor vazio. A superexpressão do mRNA e proteína foi confirmada por qPCR e imuno-histoquímica, respectivamente. As linhagens celulares transfectadas foram submetidas a ensaio de formação de colônia, de viabilidade celular, de apoptose e ciclo celular. As células C33 superexpressando HtrA1 formaram significantemente menos colônias e apresentaram redução de viabilidade celular comparadas as células sem expressão de HtrA1. Diferentemente, na linhagem HPV positiva ocorreu aumento no número de colônias nas células superexpressando HtrA1 e não houve diferença no ensaio de viabilidade celular. Esses resultados sugerem que os diferentes padrões observados nas duas linhagens celulares são decorrentes da presença do HPV na HF698 e da ausência na C33. A fim de confirmar se o aumento do número de colônias nas células HF698 superexpressando HtrA1 é decorrente da interação dessa proteína com E6, foi produzida linhagem estável de C33 com ...
Keywords: Virologia; Virus do papiloma; Doenças do virus do papiloma - Aspectos genéticos; Expressão gênica; Virology